(untitled) (Journal of the College of Basic Education, 2022)
We will provide programming performance for the proposed ideal algorithm for generating permutations by installing two components, the first and the last component, by configuring all permutations using the periodic use of the remaining elements. In this proposed method, the effort expended whether using the paper or using the calculator to! (n-2)! compared to the effort exerted by the methods used previously and in this way we used two methods Processes for finding permutations (random and regular) in finding permutations. With this paper we presented the method on a computer only by applying the proposed algorithm in the language of MATLAB.